Human Resource Management Practices and Customer Satisfaction in Hotel Industry - Bijaya Bikram Shah; Prakash Shrestha (Pravaha, 2022)
Human resource management (HRM) practices are a requirement for each modern company. They cover a number of areas and begin with the hiring of the person and continue throughout their career. The workforce is the driving force behind the lucrative and intensely competitive hospitality industry. A vital requirement for obtaining a healthy position in a highly competitive market is to utilize human resources to their fullest potential. This study aims to examine the function of human resource management techniques in the hotel industry in particular. It also discusses customer happiness, service quality, and HRM practices in hotels. The participants are 315 managers and subordinates who work in different hotels in Nepal. The statistical package for social sciences was used to code and analyze the statistics. The results show that there is a positive relationship between practices of recruitment and training, performance management, delivery of quality in service, and customer satisfaction. However, the results show that there is no relationship between compensation and the delivery of quality service. This study imply that proactive enhancement of human resource strategies is necessary for Nepalese hospitality services to increase the influence on customer satisfaction.